Quality changes in cold pressed juices after processing by high hydrostatic pressure, ultraviolet-c light and thermal treatment at commercial regimes. (August 2020) - de Souza, Vanessa Rios; Popović, Vladimir; Bissonnette, Simon; Ros, Isabel; Mats, Lili; Duizer, Lisa; Warriner, Keith; Koutchma, Tatiana
Abstract: The quality, nutritional and organoleptic parameters of cold-pressed lemonade, citrus and green juice were assessed following commercial HPP (600 MPa/3 min), UV-C light (253.7 nm/1000 L h −1 /411.4 mJ cm −2 ) and thermal treatment (75 °C/90 s) using processing regimes currently accepted in the beverage industry. Although the treatments did not affect pH, soluble solids and viscosity, they affected colour with the most pronounced change occurring in the green juice following thermal treatment. Overall, the treatments resulted in good retention (< 25% reduction) of ascorbic acid, total phenolic and antioxidant content. Notable exceptions included thermal and overdosed UV-C treatments (> 90% reduction of ascorbic acid in lemonade). HPP treatment had a neutral or positive effect on consumer acceptance of all juices, whereas thermal and overdosed UV-C treatments caused undesirable sensory changes to green and citrus juices, respectively. Overall, thermal treatment and UV-C light induced chemical changes that differentiated treated juice from the raw sample. Industrial relevance: This study verified that the currently accepted processing regimes for commercial scale HPP, UV-C light and thermal treatment affected colour, nutritional, chemical and/or sensory properties depending on the beverage matrix, suggesting that an individual product treatment approach is required for each juice. In the case of UV-C light, the effectiveness of the treatment was influenced by juice composition and UV transmission as well as the fluence level. Overdosed UV-C treatment was shown to cause undesirable effects on juice nutritional parameters. Hence, further optimization of commercial processing regimes and studies evaluating the suitability of each technology on a case by case basis should be considered. Highlights: HPP, UV-C and TT did not affect juice pH, soluble solids or viscosity. The only unacceptable change to colour occurred in green juice following TT. In general, treatments resulted in retention (> 75%) of nutritional parameters. TT and UV-C undesirably affected sensory of green and citrus juices, respectively. Specific juice formulations require a customized approach to establish processing conditions.